TARAJUMAH (Kajian terhadap Pandangan Keagamaan dan Ajaran Ahmad Rifa’i dalam Ri’ayat al-Himmat dan Husn al-Mithalab) - Ahmad Majidun; Titis Rosowulan; Zulfatun Nikmah (STAI Syubbanul Wathon Magelang, 2021)
This article seeks to explore the religious views and teachings of Ahmad Rifa'i in the books of Ri'ayat al-Himmat and Husn al-Mithalab, which are part of his Tarajumah. A descriptive analysis method with a historical approach will be used to explore religious views and teachings. This method was chosen because this article is a research library. From the analysis, it can be found that Ahmad Rifa'i's religious views are inseparable from the three main Islamic scholarships: ushuludin, fiqh and tasawuf. Meanwhile, his religious teachings are reflected in several points, which are the same as the opinions of other scholars, such as the pillars of Islam, marriage, Friday prayers, and Jamaah, and scholars who are 'alim' just. However, because there was a conflict of interest and was against the Colonial, his teachings were considered to violate Islamic teachings.